“MANTRA ABU” DALAM TEKS BHŪWANA KOSHA - I Gde Agus Darma Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Bhasma Mantra was delivered by Bhatara to Bhatari. This narrative seems very different from the early part of the text of Bhūwana Kosha. Bhasma Mantra is chapter VII of the XI chapter contained in Bhūwana Kosha. Chapter VII consists of 30 slokas. Bhasma Mantra is one part of the text of Bhūwana Kosha which explains the subject of bhasma [ashes]. The intended ash is Ongkara as a result of burning Brahma mantra into the Fire of Dampati. The Dampati fire is composed of two pairs namely the Ongkara [Purusha] and Ukara [Pradhana]. Bhasma Mantra itself is the body of Shiva. This teaching was delivered by Shiva to Uma. The practice can be found in worship rituals performed by Pandhita or sadhaka. The notion of bhasma does not only stop at ashes. Bhasma in the next stage is divided into two senses, namely sakala bhasma and niskala bhasma. Bhasma Sakala is the body, while bhasma niskala is jñāna.